2022
DOI: 10.1371/journal.pone.0273530
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes and correlates of meeting WHO recommended levels of physical activity in the UK during the COVID-19 pandemic: Findings from the HEBECO study

Abstract: Background The COVID-19 pandemic has seen repeated government enforced restrictions on movement. This study aimed to evaluate longitudinal trends in physical activity (PA) in a self-selected UK-based sample and identify the key correlates of these trends. Methods From 23 April 2020 to 30 January 2021, measures of PA engagement were collected in a sample of 1,947 UK-based adults. Generalised estimating equations (GEE) explored trends in PA engagement over time, and how sociodemographic, health and contextual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
(89 reference statements)
1
6
1
Order By: Relevance
“…Inconsistent with previous research [4,9,10], no associations were found between MVPA and cigarette use, mental health condition or physical health condition. However, this could be due to methodological constraints of the final analytic sample.…”
Section: Plos Onecontrasting
confidence: 80%
See 2 more Smart Citations
“…Inconsistent with previous research [4,9,10], no associations were found between MVPA and cigarette use, mental health condition or physical health condition. However, this could be due to methodological constraints of the final analytic sample.…”
Section: Plos Onecontrasting
confidence: 80%
“…In addition to demographic indicators, research highlights the importance of health-related covariates for MVPA during the early pandemic. Individuals with a psychiatric or physical health condition, high levels of emotional disturbance, and cigarette use reported lower MVPA outcomes during the first lockdown [ 4 , 9 , 10 ]. Busse and colleagues suggest these findings reflect a clustering effect commonly observed within epidemiological research, wherein health-related behaviours and conditions appear to co-occur [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the WHO global estimates of 2016 indicate that the percentage of adults not meeting the recommendations, 27.5%, pales in comparison to the 81% of adolescents 1. The gap between recommended amount and actual amount of physical activity even further increased during the COVID-19 pandemic,9 10 although to a varying degree for different subpopulations,11 12 thus showing the ongoing relevance of the topic.…”
Section: Introductionmentioning
confidence: 99%
“…A review of studies examining changes in PA during the pandemic found no consistent differences in changes between age groups (14). Several studies have found increasing SES inequalities in PA during the pandemic (21), both regarding level of education (20,22,23) and income (23,24). However, a Finnish study comparing responses from the same individuals before and during the pandemic found no signi cant differences in change in PA across groups with different educational levels (25).…”
mentioning
confidence: 99%